Näkökulmia sotilastoiminnan perusteiden kirkastamiseen - Mäkinen, Juha (Tiede ja ase, 2017)
In this article I examine military activities in Finland and the rest of the world from a military pedagogic perspective. I acknowledge the fact that there are some regrettably narrow and unhelpful interpretations of the duties of a soldier in our society – interpretations that show a clear lack of recognition for the social, international and global significance of military activities. e article is based on social science, leaning on my own (partly military pedagogic) research path, which provides a “ladder” with which to examine the unfortunately crisis-ridden core of military activities. e reason why military activities are currently in crisis is, as I assert, because of the “postmodern” narrowing of the significance of military operations and activities, distortions in the orientational and motivational basis of the role of soldiers, and deficiencies in education and self-education.